Effects of vitamin A on intramuscular fat development in beef cattle: A meta-analysis - Li, Wei; Wang, Fang; Sun, Fang; Qu, Yongli; Liu, Chunhai; Han, Yongsheng; Wang, Hongbao; Jiang, Botao; Zhong, Peng; Wang, Jiahui; Song, Xueying; Huang, Meng; et al. (Frontiers in Veterinary Science, 2023)
Vitamin A is a fat-soluble vitamin, which is the basic substance to maintain healthy vision and main physiological functions of cattle. Results in previous studies regarding the effect of vitamin A on intramuscular fat varied. The aim of this meta-analysis was to generate a more comprehensive understanding of the relation between vitamin A and intramuscular fat and to provide potential clues for future research and commercial practice. Electronic databases of Medline and Ovid were systematically searched. Studies investigating the relationship between vitamin A and intramuscular fat were included. Standardized mean difference (SMD) of intramuscular fat percentage and score, with their respective 95% confidence interval (CIs) were calculated. The heterogeneity and publication of bias were evaluated. A total of 152 articles were identified through the databases search. 7 articles were confirmed for inclusion in this meta-analysis. With regard to the analysis of IMF percentage, the SMD was -0.78 (-2.68, 1.12) (Q=246.84, p < 0.01). The SMD of IMF score was 1.25 (-2.75, 5.25) (Q=87.20, p < 0.01). Our meta-analysis indicates that the addition of vitamin A could decrease intramuscular fat in cattle steers.